Questions Metacognitive Domains in Indonesian XII Grade Textbooks - Rahmania Rahmania; Ramly Ramly; Sultan Sultan (HUMAN: South Asian Journal of Social Studies, 2021)
Abstract. This study aims to: (1) describe the results of the analysis of the form of metacognitive questions in the form of strategic knowledge in the XII grade Indonesian language textbooks; (2) describe the results of the analysis of the form of metacognitive questions in the form of cognitive tasks, which include contextual and conditional knowledge in the XII grade Indonesian language textbook; (3) describe the results of the analysis of the form of metacognitive questions in the form of self-knowledge in the Indonesian language textbook class XII. This type of research is a qualitative descriptive study. This research was conducted in class XII Indonesian textbooks. Data collection was carried out during December 2020 - April 2021. The research design used was descriptive qualitative. The focus of this research, namely questions that contain metacognitive knowledge in the XII grade Indonesian language textbooks compiled by the Ministry of Education and Culture in 2018. The source of research data, namely questions about the XII grade Indonesian textbooks The data collection technique was carried out by reading all the questions in the Indonesian language textbook for class XII, identifying and analyzing textbook questions, marking questions, sorting out various kinds of questions, moving data, and categorizing the data. The research instrument used was the observation guide table instrument. The results of the study revealed the form of strategic knowledge questions, the form of knowledge questions about cognitive tasks, and the form of self-knowledge questions. The forms of strategic knowledge questions found consisted of (1) PS / Pul, (2) PS / Ex, (3) PS / Renc. (4) PS / Ela, and (5) PS / Pema. The form of knowledge questions about cognitive tasks that were found consisted of, (1) PTK / Konli, (2) PTK / Kolas, (3) PTK / Konis, (4) PTK / Koding, (5) PTK / Kondis, (6) ) PTK / Kotik, (7) PTK / Kofra, (8) PTK / Kobus, (9) PTK / Kokla, and (10) PTK / Koda. The forms of self-knowledge questions that were found consisted of, (1) PD / Nimi, (2) PD / Kedi, and (3) PD / Tula. Keywords: Strategic Knowledge, Cognitive Tasks, Self-Knowledge